The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/1467-8268.12458
|View full text |Cite
|
Sign up to set email alerts
|

Does fiscal tightening (loosening) reduce public debt?

Abstract: This study examined the effect of fiscal tightening and loosening on the public debt of sub‐Saharan African (SSA) countries. To achieve this, the study employed a two‐step approach. In the first step, the effect of government primary balance on public debt was examined; while in the second step, the primary balance was disaggregated into its surplus and deficit components with the effect of each component on public debt examined. By utilising data covering a panel of 37 SSA countries for the period 2008 to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…High‐income countries are expected to collect more taxes than developing countries because they have better organization of tax administration, better institutions, and greater demand for public goods and services (Alagidede et al, 2018; Caldeira et al, 2019; Lotz & Morss, 1967; Okombi, 2021; Pessino & Fenochietto, 2010). However, Abubakar (2020) highlights a negative relationship between tax pressure and economic growth. Moreover, according to EN growth theorists (Hanushek, 2005; Mankiw et al, 1992), human capital seems to be the determining factor of economic growth.…”
Section: Methodsmentioning
confidence: 99%
“…High‐income countries are expected to collect more taxes than developing countries because they have better organization of tax administration, better institutions, and greater demand for public goods and services (Alagidede et al, 2018; Caldeira et al, 2019; Lotz & Morss, 1967; Okombi, 2021; Pessino & Fenochietto, 2010). However, Abubakar (2020) highlights a negative relationship between tax pressure and economic growth. Moreover, according to EN growth theorists (Hanushek, 2005; Mankiw et al, 1992), human capital seems to be the determining factor of economic growth.…”
Section: Methodsmentioning
confidence: 99%
“…Using 2000-16 panel data for 32 SSA countries, Mupunga and Ngundu (2020) found a positive and significant response of primary balances to increases in debt levels, thus implying fiscal sustainability of public debt. Based on data for 37 SSA countries for 2008-17, Abubakar (2020) found that fiscal tightening led to a decline in public debt while fiscal loosening increased public debt. However, in a more current study using data for 2010-20 for a panel of 45 SSA countries, Olaoye and Olomola (2022) found SSA's public debts to be weakly sustainable.…”
Section: Overview Of Empirical Evidence On Fiscal Sustainabilitymentioning
confidence: 99%
“…Existing research on the influencing factors of the scale of local government debt has approached the question from fiscal (Abubakar, 2020) and taxation (Ukeme & Ifayemi, 2020) perspectives, but few studies have paid attention to the impact of government official corruption on the scale of local government debt and its associated mechanism. Second, most research on corruption and macroeconomics focuses on the relationship between corruption and economic growth (Gr€ undler & Potrafke, 2019), investment (Brada et al, 2019), and so on.…”
Section: Introductionmentioning
confidence: 99%